Model Pembelajaran Every One Is a Teacher Here, Scaffolding Meningkatkan Keterampilan Sosial Siswa - Agus Setiadi; Tedi Rusman; I Komang Winatha (JEE (Jurnal Edukasi Ekobis), 2018)
This research is motivated by the lack of social skills of the students and examined the differences of the social skills in which the learning uses  “Everyone Is a Teacher Here model and Scaffolding” of the eighth grade students of SMP N 20 Bandar Lampung. The aim is to find out the differences in the students' social skills using the “Everyone Is a Teacher Here and Scaffolding” learning models. The method used in this study is Randomized Subject Post Test Only Control Group Design. The population in this study were 327 students with a sample of 60 students. The sampling technique is the random samplings cluster while the data collection used was observation. The hypotheses testings used is two independent sample T tests, and the results of the test show there are differences in social skills of the students whose learning uses  “Everyone Is a Teacher Here model and Scaffolding” learning models. Penelitian ini dilatarbelakangi oleh rendahnya keterampilan sosial siswa serta mengkaji tentang perbedaan keterampilan sosial yang pembelajranya menggunakan model pembelajaran Everyone Is a Teacher Here dan Scaffolding siswa kelas VIII SMP N 20 Bandarlampung. Tujuanya untuk mengetahui perbedaan keterampilan sosial siswa dengan menggunakan model pembelajaran Everyone Is a Teacher Here dan Scaffolding. Metode yang digunakan dalam penelitian ini adalah dengan Randomaized  Subject Post Test Only Control Grup Design. Populasi dalam penelitian ini sebanyak 327 siswa dengan sample sebanyak 60 siswa. teknik pengambilan samplenya adalah Cluster random Sampling  sedangkan pengambilan datanya menggunakan observasi. Pengujian hipotesis menggunakan t test dua sample independent, dan hasil pengujian datanya menunjukan ada perbedaan keterampilan sosial siswa yang pembelajaranya menggunakan model pembelajaran Everyone Is a Teacher Here dan Scaffolding. Kata kunci: keterampilan sosial, model pembelajaran everyone is a teacher here dan scaffolding